2019
DOI: 10.1002/hpm.2781
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analyses of the global acceptability rates of male intimate partner violence (IPV) against women based on World Values Survey data

Abstract: Summary Major international organizations like UN Women and the World Health Organization (WHO) estimate that nowadays, more than one‐third of all women in the world suffer male intimate partner violence (IPV) at some point in their lives and that eliminating the societal acceptancy of that violence is a major element in combatting it. While there is consensus that IPV has disastrous public health consequences, so far, little is known about the drivers of IPV acceptability rates. This article therefore analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…Relating to the acceptability of VAW and IPVAW, some general surveys carried out in the European Union [ 32 , 33 ] showed that the majority of the people considered IPVAW as unacceptable in all circumstances and always punishable by law, with this rejection gaining ground over time; only about 1–2% of the people interviewed thought this violence as acceptable in certain circumstances or even in all circumstances. In line with these findings, Tausch [ 30 ] analyzed data from the World Values Survey project, and observed that some Western European countries (such as Italy or Norway) are among those with the lowest rates of acceptance of IPVAW. However, it is important to remark that, despite this rejection, European Union surveys [ 11 , 29 , 33 , 34 ] showed a high prevalence of IPVAW victim blaming attitudes in the EU, and the number of people who consider the provocative behavior of women as a cause of such violence actually increased between these two surveys, from 46.1% in 1999 to 52% in 2010.…”
Section: Introductionmentioning
confidence: 90%
“…Relating to the acceptability of VAW and IPVAW, some general surveys carried out in the European Union [ 32 , 33 ] showed that the majority of the people considered IPVAW as unacceptable in all circumstances and always punishable by law, with this rejection gaining ground over time; only about 1–2% of the people interviewed thought this violence as acceptable in certain circumstances or even in all circumstances. In line with these findings, Tausch [ 30 ] analyzed data from the World Values Survey project, and observed that some Western European countries (such as Italy or Norway) are among those with the lowest rates of acceptance of IPVAW. However, it is important to remark that, despite this rejection, European Union surveys [ 11 , 29 , 33 , 34 ] showed a high prevalence of IPVAW victim blaming attitudes in the EU, and the number of people who consider the provocative behavior of women as a cause of such violence actually increased between these two surveys, from 46.1% in 1999 to 52% in 2010.…”
Section: Introductionmentioning
confidence: 90%
“…Multiple comparisons between groups yielded two homogeneous sets for all dimensions: lower acceptance [Set 1] and higher acceptance [Set 2]. Adolescents (<18) and older adults (≥60) performed in higher acceptance, whereas middle-aged adults and young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) performed in lower acceptance, except in F3-VP, where young adults performed in the higher acceptance set with adolescents and older adults. 1 Set 1 = lower acceptance of IPVAW; Set 2 = higher acceptance of IPVAW.…”
Section: Explicit Measures Of Attitude Towards Ipvawmentioning
confidence: 99%
“…Here again, two homogeneous sets are identified for the variables whose differences are statistically significant: lower acceptance [Set 1, i.e., higher perceived frequency] and higher acceptance [Set 2, i.e., lower perceived frequency]. Regarding perceived frequency of psychological abuse, attitudes differ between age groups by adopting a U-shape distribution: adolescents (<18) and older adults (≥60) performed in Set 2, whereas young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and middle-aged adults (30-59) performed in Set 1. In the case of violent threats, only older adults performed in Set 2 whereas all the other groups performed in Set 1.…”
Section: Other Evidence About Attitudes Towards Ipvawmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Tausch (2019) analyzed data from the WVS, specifically data from 72 countries around the world, and observed that some Western European countries (such as Italy or Norway) are among those with the lowest rates of acceptance of IPVAW.…”
Section: Introductionmentioning
confidence: 99%